2020
DOI: 10.1253/circrep.cr-19-0105
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Clopidogrel Non-Use Worsen Prognosis of Critical Limb Ischemia Patients After Revascularization

Abstract: Background: Critical limb ischemia (CLI) patients have high risk for major adverse cerebrovascular and cardiovascular events. This study investigated the risk factors of cerebrovascular or cardiovascular death in CLI patients with concomitant coronary artery disease (CAD). Methods and Results: The association between baseline characteristics and cerebrovascular or cardiovascular death ≤2 years after revascularization for CLI was investigated in 137 CLI patients who previously underwent successful revasculariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Malnutrition, as defined by a GNRI <92, was significantly associated with cerebrovascular or cardiovascular death. 64 In another clinical study, investigating 104 patients with either PAH or chronic thromboembolic PH, the incidence of PH rehospitalization was higher in the low GNRI group (<92) than that in the high GNRI group (≥92). The cumulative event-free rate was significantly lower in the low GNRI group.…”
Section: Frailty and Atrial Fibrillationmentioning
confidence: 96%
See 1 more Smart Citation
“…Malnutrition, as defined by a GNRI <92, was significantly associated with cerebrovascular or cardiovascular death. 64 In another clinical study, investigating 104 patients with either PAH or chronic thromboembolic PH, the incidence of PH rehospitalization was higher in the low GNRI group (<92) than that in the high GNRI group (≥92). The cumulative event-free rate was significantly lower in the low GNRI group.…”
Section: Frailty and Atrial Fibrillationmentioning
confidence: 96%
“…63 Recently, we reported that malnutrition, assessed using GNRI, affected the prognosis of patients with either PAD/CLI or PAH. 64,65 We investigated 137 CLI patients who had previously undergone successful revascularization for CAD. Twentythree (17%) patients died, and the GNRI level among the deceased group was significantly lower than that among the surviving group.…”
Section: Frailty and Atrial Fibrillationmentioning
confidence: 99%
“…However, the value of the GNRI score by continuous analysis in predicting amputation was not statistically significant. Moreover, malnutrition defined by the GNRI <92 was significantly associated with cerebrovascular or cardiovascular mortality in CLTI patients after revascularization ( 24 ). These findings suggest that nutritional status determined by the GNRI may provide some important prognostic information in patients with lower extremity PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status has been found to affect the outcome of various diseases [2][3][4]. Especially, malnutrition is an important factor in frailty and sarcopenia, which have become major clinical problems in recent years, and has been reported to be associated with poor prognosis for patients with chronic diseases such as heart and renal failure [5,6].…”
mentioning
confidence: 99%